Comparison of ustekinumab, infliximab and combination therapy in moderately to severely active ulcerative colitis – a study protocol of a randomized, multicenter, head-to-head COMBO-UC trial - Talar-Wojnarowska, Renata; Fabisiak, Adam; Zatorski, Hubert; Płoszka, Katarzyna; Błaziak, Katarzyna; Fendler, Wojciech; Rydzewska, Grażyna; Małecka-Wojciesko, Ewa; Eder, Piotr (Frontiers in Medicine, 2024)
Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease with a complex etiology that affects the large intestine. Characterized by chronic, bloody diarrhea, UC can lead to severe complications, including an increased risk of colorectal cancer. Despite advancements in conservative treatment, including biologics like anti-TNF agents and ustekinumab (UST), many patients do not achieve full remission. Dual targeted therapy (DTT) combining infliximab (IFX) and UST is a promising approach to improve treatment outcomes.Methods: This prospective, randomized, multicenter, head-to-head controlled trial will evaluate the efficacy and safety of UST, IFX, and combination therapy (UST+IFX) in 172 patients with moderate to severe active UC across eight gastroenterology centers in Poland. The study includes a 14-16 week remission induction period followed by a 52-week maintenance phase. Patients will be randomly assigned to one of three treatment arms: IFX monotherapy, UST monotherapy, or IFX+UST combination therapy. Primary endpoint is clinical and endoscopic remission post-induction. Secondary endpoints include clinical response, biochemical remission, histological remission, and quality of life assessments using the Inflammatory Bowel Diseases Questionnaire and 36-Item Short Form Survey. Safety will be monitored through adverse event and serious adverse event reporting. Discussion: This trial aims to determine whether combining IFX and UST can achieve higher remission rates and better long-term outcomes compared to monotherapy. The results could provide crucial insights into the optimal use of biologic agents in UC treatment, potentially establishing DTT as a standard therapy. The study's design, including extensive follow-up and robust endpoint measures, will contribute to understanding the therapeutic potential and safety profile of this combination therapy